Katie Louchheim papers - Louchheim, Katie, 1903-; Louchheim, Walter C. (Walter Clinton), 1899-1973.; Scofield, Adele Joseph
Correspondence, memoranda, journals (1942-1981), family papers, speeches, writings, interviews, subject files, scrapbooks, newspaper clippings, photographs, memorabilia, and other papers relating primarily to Louchheim's role in Democratic party politics, particularly as vice-chair of the Democratic National Committee (1956-1960), and her duties as deputy assistant secretary of state, especially with the Bureau of Educational and Cultural Affairs, Office of Community Advisory Services, and Bureau of Public Affairs at the U.S. Dept. of State. Other papers relate to her work with United Nations Relief and Rehabilitation Administration and Lady Bird Johnson's landscape beautification projects, women's rights, social life in Washington, D.C., and her writings. Family papers are chiefly those of her mother, Adele Joseph Scofield, pertaining to her charitable and political interests, but also include letters of Louchheim's first husband, banker Walter C. Louchheim, written while attending the Bretton Woods Conference in 1944.
Correspondents include Walter H. Annenberg, Barry Bingham, Mary Caperton Bingham, Hale Boggs, Lindy Boggs, Evangeline Bruce, Bennett Cerf, Angier Biddle Duke, Robin Chandler Lynn Duke, India Edwards, Henry Ehrlich, Albert Gore, Pauline La Fon Gore, Florence Jaffrey Hurst Harriman, Hubert H. Humphrey, Lady Bird Johnson, Abigail Q. McCarthy, Eugene J. McCarthy, Stephen A. Mitchell, Sam Rayburn, Edwin O. Reischauer, Haru Matsukata Reischauer, Bess Wallace Truman, and Charles E. Wyzanski. Other persons represented, particularly in Louchheim's journals, include Paul M. Butler, Liz Carpenter, William O. Douglas, Lyndon B. Johnson, John F. Kennedy, Robert F. Kennedy, James Reston, Dean Rusk, Theodore Sorensen, Adlai E. Stevenson, and Harry S. Truman. Includes interviews conducted by Louchheim in 1985 and 1986 with Kitty Carlisle, Betty Furness, Constance Baker Motley, and others for a book on prominent women.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Government official, Democratic party leader, and author. Born Kathleen Scofield; married first, Walter C. Louchheim; second, Donald Klopfer. Died 1991.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Annenberg, Walter H., -- 1908-2002 -- Correspondence; Bingham, Barry, -- 1906-1988 -- Correspondence; Bingham, Mary Caperton, -- 1904- -- Correspondence; Boggs, Hale, -- 1914-1972 -- Correspondence; Boggs, Lindy, -- 1916-2013 -- Correspondence; Bruce, Evangeline -- Correspondence; Butler, Paul M. -- 1905-1961.; Carlisle, Kitty, -- 1910-2007 -- Interviews; Carpenter, Liz; Cerf, Bennett, -- 1898-1971 -- Correspondence; Douglas, William O. -- 1898-1980.; Duke, Angier Biddle, -- 1915-1995 -- Correspondence; Duke, Robin Chandler Lynn -- Correspondence; Edwards, India -- Correspondence; Ehrlich, Henry -- Correspondence; Furness, Betty, -- 1916-1994 -- Interviews; Gore, Albert, -- 1907-1998 -- Correspondence; Gore, Pauline La Fon -- Correspondence; Harriman, Florence Jaffray, -- 1870-1967 -- Correspondence; Humphrey, Hubert H. -- 1911-1978 -- Correspondence; Johnson, Lady Bird, -- 1912-2007.; Johnson, Lady Bird, -- 1912-2007 -- Correspondence; Johnson, Lyndon B. -- 1908-1973.; Kennedy, John F. -- 1917-1963.; Kennedy, Robert F., -- 1925-1968.; McCarthy, Abigail Q. -- Correspondence; McCarthy, Eugene J., -- 1916-2005 -- Correspondence; Mitchell, Stephen A. -- 1903-1974 -- Correspondence; Motley, Constance Baker, -- 1921- -- Interviews; Rayburn, Sam, -- 1882-1961 -- Correspondence; Reischauer, Edwin O. -- 1910-1990 -- Correspondence; Reischauer, Haru Matsukata, -- 1915- -- Correspondence; Reston, James, -- 1909-1995; Rusk, Dean, -- 1909-1994.; Sorensen, Theodore C; Stevenson, Adlai E. -- 1900-1965.; Truman, Bess Wallace -- Correspondence; Truman, Harry S., -- 1884-1972.; Wyzanski, Charles E. -- 1906- -- Correspondence; Louchheim family; Schofield family; United States. -- Bureau of Educational and Cultural Affairs; United States. -- Department of State. -- Office of Community Advisory Services; United States. -- Department of State. -- Bureau of Public Affairs; Democratic National Committee (U.S.); Democratic Party (U.S.); United Nations Relief and Rehabilitation Administration; Landscape protection; Women -- Political activity -- United States; Women's rights; United States -- Foreign relations -- 1945-1989.; United States -- Politics and government -- 1945-; Washington (D.C.) -- Social life and customs; Authors; Public officials